JAKARTA CONSUMER RESPONSE DURING THE COVID-19 PANDEMIC - Muhammad Dhany Afrihan (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
A critical circumstance we have around the world include Indonesia since March2020 named the COVID-19 pandemic, with the lockdown, semi-lockdownsituation, and social distancing impacted economic instabilities of the nations andchange in market dynamics. As we know, market competitiveness, economicintegration, and growth are driven by consumers. This crisis makes consumersworldwide, including Indonesia, experience behavior transformation, improviseand learn new habits. Despite the situation, this research would like to examine more deeper how consumers in Indonesia respond to threats such as the COVID19 pandemic that disrupt consumers’ routine and lives and the immediate effectsof the COVID-19 pandemic on consumption and consumers’ behavior inIndonesia. This research conducts a structured interview with twenty-threeinformants with open-ended questions to get qualitative data as primary data andsecondary data from magazines, national newspapers, and the internet. Thisresearch aims to formulate consumers’ adaptive response in Indonesia in moredetail by having a unique country specific framework. The empirical findings ofthis research identified that the COVID-19 pandemic is external threat that bringdisruption and utter unique responses to Indonesia’s consumers with storehouse,pent-up demand and accepting digital technology. In addition, this researchcould also help company to develop specific business strategies to supportconsumers and country in this pandemic situation.